Engine Performance and Emission Analysis of TiO2 Nanoparticle-Enhanced Waste Cooking Oil Biodiesel - Neupane, Milan; Sharma, Shahil; Dahal, Prajwal; Devkota, Lochan Kendra; Dhakal, Rabindra Prasad (Himalayan Journal of Applied Science and Engineering, 2026)
This study has investigated the effect of Titanium dioxide nanoparticles (TiO2) on the performance and emission characteristics of a Waste Cooking Oil (WCO) biodiesel-diesel blend. Biodiesel was prepared from WCO using an alkali-catalyzed transesterification process, while TiO2 nanoparticles were prepared by the sol-gel method and characterized using XRD, UV-Vis spectroscopy, SEM, and EDS. Tests were conducted on a single-cylinder CI engine, operated at 1500 rpm, using neat diesel (D100), B20, and B20 with 50 ppm TiO2 (B20T50) nanoparticles. The results indicate that the base B20 blend gave marginally lower brake power and brake thermal efficiency compared to diesel, which is mainly due to its lower calorific value. The addition of TiO2 nanoparticles helped in improving the combustion of fuel, thus giving higher brake power and thermal efficiency and resulting in reduced BSFC under all load conditions. Regarding emissions, biodiesel blends resulted in lesser CO and HC emissions, and further reductions were registered for B20T50. While CO2 emissions were increased, NOx emissions decreased compared with the base B20 blend due to improved and controlled combustion characteristics.